THE INFLUNCE OF YOU TUBE CONTENT ON ENGLISH VOCABULARY DEVELOPMENT IN CHILDREN - Adhamova Mohlaroy Nodirbek qizi (Bright Mind Publishing, 2025)
This article examines the role of YouTube content in developing English vocabulary among young children through classroom action research and qualitative analysis. Findings show significant vocabulary improvement after structured exposure to themed YouTube videos, supported by observations of natural language use in early childhood. The study also highlights the value of traditional methods such as storytelling and flashcards. Overall, the research concludes that combining digital media with guided instruction creates an effective, engaging environment for children’s early English vocabulary development.
Keywords: Digital learning, multimodal acquisition, early childhood development, learning strategies, interactive instruction, child development, digital pedagogy.